Interaction of germline variants in a family with a history of early‐onset clear cell renal cell carcinoma. Issue 3 (24th January 2019) - Nicolas, Emmanuelle; Demidova, Elena V.; Iqbal, Waleed; Serebriiskii, Ilya G.; Vlasenkova, Ramilia; Ghatalia, Pooja; Zhou, Yan; Rainey, Kim; Forman, Andrea F.; Dunbrack, Roland L.; Golemis, Erica A.; Hall, Michael J.; et al.
Abstract: Background: Identification of genetic factors causing predisposition to renal cell carcinoma has helped improve screening, early detection, and patient survival. Methods: We report the characterization of a proband with renal and thyroid cancers and a family history of renal and other cancers by whole‐exome sequencing (WES), coupled with WES analysis of germline DNA from additional affected and unaffected family members. Results: This work identified multiple predicted protein‐damaging variants relevant to the pattern of inherited cancer risk. Among these, the proband and an affected brother each had a heterozygous Ala45Thr variant in SDHA, a component of the succinate dehydrogenase (SDH) complex. SDH defects are associated with mitochondrial disorders and risk for various cancers; immunochemical analysis indicated loss of SDHB protein expression in the patient's tumor, compatible with SDH deficiency. Integrated analysis of public databases and structural predictions indicated that the two affected individuals also had additional variants in genes including TGFB2, TRAP1, PARP1, and EGF, each potentially relevant to cancer risk alone or in conjunction with the SDHA variant. In addition, allelic imbalances of PARP1 and TGFB2 were detected in the tumor of the proband. Conclusion: Together, these data suggest the possibility of risk associated with interaction of two or more variants. Abstract : This manuscript addresses the growing need to assign cancer risk to rare variants of uncertain significance. In this manuscript, we have described a proband with a personal history of early‐onset renal and thyroid cancers, and a family history of renal and other cancers. Our data suggest the possibility of risk associated with interaction of two or more reported variants and provides the basis for analysis in other families.